2011
DOI: 10.1103/physrevb.83.024406
|View full text |Cite
|
Sign up to set email alerts
|

Transverse susceptibility as a probe of the magnetocrystalline anisotropy-driven phase transition inPr0.5Sr0.5CoO

Abstract: Half-doped Pr 1-x Sr x CoO 3 (x=0.5) displays anomalous magnetism most notably manifest in the field-cooled magnetization versus temperature curves under different applied cooling fields.Recently, an explanation was advanced that a magnetocrystalline anisotropy transition driven by a structural transition at 120 K is the origin of this behavior. In this paper, we further elucidate the nature of the magnetic anisotropy across the low temperature phase transition in this material by means of transverse susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…A detailed description of the TS measurements can be found in our earlier papers. [19][20][21] Figures 3a and 3b show the TS spectra of the YIG/Pt and YIG/C 60 /Pt samples at room temperature. As the DC magnetic field was swept from positive to negative saturation, two peaks were observed in the positive quadrant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the TS measurements can be found in our earlier papers. [19][20][21] Figures 3a and 3b show the TS spectra of the YIG/Pt and YIG/C 60 /Pt samples at room temperature. As the DC magnetic field was swept from positive to negative saturation, two peaks were observed in the positive quadrant.…”
Section: Resultsmentioning
confidence: 99%
“…Over the years, we have established the TS technique as a direct, accurate probe of effective magnetic anisotropy field (H K ) for a wide range of magnetic materials. [19][20][21] In this method, sample is placed inside an inductive coil which is part of the TDO circuit. An RF perturbation field is applied perpendicular to the DC field.…”
Section: Resultsmentioning
confidence: 99%
“…19 Evidences of the interplay between the magnetic and crystal structures were obtained from transverse susceptibility and magnetostriction measurements which point to likely changes in the magnetocrystalline anisotropy at T S1 . [12][13][14]20 Lorentz Transmission Electron Microscopy (LTEM) images reported by Uchida et al also suggested a reorientation of the magnetization axis by 45º when studying the evolution of the magnetic domain structure under electronbeam. 21 The importance of the spin-lattice coupling has been also confirmed by means of xray magnetic circular dichroism (XMCD) experiments at the Co L 2,3 edges.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of a second magnetic transition and intriguing step-like behavior of the magnetization, which decreases or increases depending on the magnitude of the applied field, [12][13][14][15][16] was followed by the detection of structural anomalies at the same temperature by…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation